Analisa Variabel Kunci Pengembangan Infrastrukur Pariwisata di Wilayah Utara Perbatasan Indonesia (Studi Kasus: Kabupaten Nunukan) - Eko Prihartanto; Efraim Bavo Priyana (Journal of Research and Technology, 2022)
The province of North Kalimantan has a direct boundary with the eastern part of Malaysia, including the Nunukan Regency with the Sabah Region. Nunukan Regency has a number of attractive tourism places for tourists to visit, but they are still minimal in the availability of supporting infrastructure, so this research was conducted to obtain a model to support tourism infrastructure. The methodology used in this research is descriptive qualitative, by obtaining data from questionnaires and interviews with respondents from government agencies, travel business actors, to communities around tourist attractions. The object of this research is a tourist spot in Nunukan Regency, then an analysis is carried out using Interpretive Structural Modeling (ISM). The result of this research is that a model is obtained that provides the key variables that place the variable in the top position in the model. The ISM model obtained places the availability of the types of facilities that have been provided for a place to stay for visitors. This is not without reason because from interviews it was found that tourists want a place to stay overnight to be able to enjoy the natural atmosphere with their family. From the research it was also found that infrastructure remains a priority in supporting tourism objects.